Progress of MWCNT, Al2O3, and CuO with water in enhancing the photovoltaic thermal system. (8th November 2019) - Sangeetha, Manimaran; Manigandan, Sekar; Chaichan, Miqdam T.; Kumar, Vasanth
Summary: Hybrid photovoltaic thermal system is an effective method to convert solar energy into electrical and thermal energy. However, its effectiveness is widely affected due to the high temperature of photovoltaic panel, and it can be minimized by employing nanofluids to the PV/T systems. In this research, the effect of various nanoparticles on the PV/T systems was studied experimentally. The nanofluids Al2 O3, CuO, and multiwall carbon nanotube (MWCNT) were dispersed with water at different volume fractions of 0, 0.5, 1, 2.5, and 5 (vol%) using ultrasonication process. The effect of nanomaterials on viscosity and density was classified. All tests were carried out in an outdoor laboratory setup for calibrating the PV temperatures, thermal conductivity, electrical power, electrical efficiency, and overall efficiency. In addition, the energy analyses were also made to estimate the loss of heat owing to the nanofluids. Results show that use of the nanofluid increased the electric power and electrical efficiency of PV/T compared with water. Furthermore, MWCNT and CuO reduced the cell temperature by 19%. Consequently, the nanofluids MWCNT, Al2 O3, and CuO produced the impressive values of 60%, 55%, and 52% increase in an average electrical efficiency than conventional PV. Particularly, the MWCNT produced superior results compared with other materials. It is evidently clear from the result that the introduction of the nanofluid increases the thermal efficiency without adding any extra energy to the system. Moreover, insertion of Al2 O3, CuO, and MWCNT on PV/T system increases the exergy efficiency more than conventional PV module.